2005
DOI: 10.1111/j.1464-410x.2005.05207.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic endoureterotomy

Abstract: OBJECTIVE To highlight the current status of ureteroscopic endoureterotomy (UE) by reporting extensive experience with the endoscopic management of ureteric strictures, with special emphasis on factors determining success, and by reviewing publications on the minimally invasive management of ureteric strictures. PATIENTS AND METHODS The study comprised 50 patients (mean age 53 years, range 18–85, equal sex distribution) with ureteric strictures of varying causes; all had their stricture treated endoscopically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 100 publications
0
28
0
Order By: Relevance
“…Razdan and associates 8 have shown that double stent placement may increase the likelihood of success when encountering a difficult stricture with previously failed intervention. Some authors advocated using two stents, which may act as a mold around which the ureter reforms with wide lumen.…”
Section: Discussionmentioning
confidence: 98%
“…Razdan and associates 8 have shown that double stent placement may increase the likelihood of success when encountering a difficult stricture with previously failed intervention. Some authors advocated using two stents, which may act as a mold around which the ureter reforms with wide lumen.…”
Section: Discussionmentioning
confidence: 98%
“…Endourological reconstruction of these pathologies seldom suffices. [5] In the presence of a salvagable renal unit, uretereoneocystostomy with or without Boari flap remains the most desired option for restoration of ureteral continuity. Contrastingly, in iatrogenic lower ureteric injuries conventional practice entails attempting a temporising measure (ureteral stent or nephrostomy) primarily, deferring definitive reconstruction for an interval of six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 Acucise endoureterotomy is more commonly used for treatment of short-segment ureteric strictures that develop after urologic procedures such as pyeloplasty, renal transplantation, ureterocystoneostomy, ureteroenteric anastomosis, calico-ureterostomy, and transurethral resection of the ureteral orifice. 5 There have been case reports of Acucise endoureterotomy used for the treatment of stricture formation after gynecologic procedures such as hysterectomy, 6,7 but we were unable to identify any reports of the use of this procedure after laparoscopic ureteric injury.…”
Section: Discussionmentioning
confidence: 99%
“…1 The device consists of an inflatable balloon and monopolar electrical wire. A retrograde pyelogram is performed to identify the area of stricture, and the Acucise device is placed into the ureter along a guidewire inserted by a cystoscope through the bladder.…”
Section: Case Reportmentioning
confidence: 99%